2019
DOI: 10.1002/eji.201948343
|View full text |Cite
|
Sign up to set email alerts
|

A pan‐inflammatory microRNA‐cluster is associated with orbital non‐Hodgkin lymphoma and idiopathic orbital inflammation

Abstract: Non‐Hodgkin orbital lymphoma (NHOL) and idiopathic orbital inflammation (IOI) are common orbital conditions with largely unknown pathophysiology that can be difficult to diagnose. In this study we aim to identify serum miRNAs associated with NHOL and IOI. We performed OpenArray® miRNA profiling in 33 patients and controls. Differentially expressed miRNAs were technically validated across technology platforms and replicated in an additional cohort of 32 patients and controls. We identified and independently val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…To date, only two studies have reported miRNA profiles of orbital malignant lymphoma, including diffuse large B-cell lymphoma [54,55]. Recently, Laban et al showed that seven (miR-140-5p, miR-148a-3p, miR193a-5p, miR-223-3p, miR-29a-3p, miR-365a-3p, and U6 snRNA) of 399 miRNAs analyzed in a panel were upregulated in the serum of patients with non-Hodgkin lymphomas, including diffuse large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only two studies have reported miRNA profiles of orbital malignant lymphoma, including diffuse large B-cell lymphoma [54,55]. Recently, Laban et al showed that seven (miR-140-5p, miR-148a-3p, miR193a-5p, miR-223-3p, miR-29a-3p, miR-365a-3p, and U6 snRNA) of 399 miRNAs analyzed in a panel were upregulated in the serum of patients with non-Hodgkin lymphomas, including diffuse large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small noncoding regulatory RNAs whose compositional changes are associated with human pathophysiological processes, such as inflammation and cancer, etc. Bashant et al identified a paninflammatory miRNA-cluster, especially miR-223, that was upregulated in patients with OIP compared to controls [ 54 ]. MiR-223 derived from neutrophils in blood is a significant source of serum miRNAs [ 55 ].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…MiR-223 derived from neutrophils in blood is a significant source of serum miRNAs [ 55 ]. In addition, a positive correlation was shown between the size of neutrophil cells and serum miR-223 levels in OIP patients [ 54 ]. These analyses suggested that changes in blood leukocyte composition may underlie increased miRNA clusters in blood in patients with OIP and that serum miRNA clusters correlate with neutrophil status.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Several investigators suggested that the development of lymphoma, especially EMZL, may be associated with longterm chronic infections of the patients, such as chlamydia infection, helicobacter pylori infection, and chronic hepatitis [25][26][27][28] . The immune status was also considered to be associated with the development of orbital lymphoma [29][30] .…”
Section: Orbital Lymphoma Clinical Characteristicsmentioning
confidence: 99%